CATALAN COLLOCATIONS TAU METHOD FOR SOLUTION OF FRACTIONAL INTEGRO-DIFFERENTIAL EQUATIONS - Isiyaku, Musa; Amos, Jerry; Oladoja, Adebayo S.; Chukkol, Y. B.; Jingi, Bala M. (FUDMA JOURNAL OF SCIENCES, 2025)
This article is concern with the numerical solution of Fractional order Fredholm Integro-differential Equations using Catalan tau collocation method. The concept of Catalan tau collocation method was implemented on some of fractional Fredholm integro-differential equations to illustrate the efficienciency and practicability of the method. Fractional derivatives in Riemann-Liouvilles sense were adopted throughout this article.. The results showed the reliable, efficacy and accuracy that the method exhibited for this kind of problems when compared to the analytic solutions.
Keywords: Collocation Tau Method; Fractional Fredholm Integro-differential Equations; Fractional derivatives